2006
DOI: 10.1136/jcp.2005.028613
|View full text |Cite
|
Sign up to set email alerts
|

Liver infiltrating mononuclear cells in children with type 1 autoimmune hepatitis

Abstract: Objective: To investigate infiltrating cells in the liver of children with type 1 autoimmune hepatitis (AH-1). Methods: liver biopsies from 24 untreated AH-1 patients (14 children, 10 adults), five patients with hepatitis C virus related chronic hepatitis (HCV), and 10 control liver specimens (CL) were processed for immunohistochemical cell characterisation. Results: Two different cell distribution patterns were detected in the liver of patients with AH-1: (1) CD4 + and CD20+ cells were found in the central ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…Through the same functional study based on ROS generation, oxygen metabolism of circulating monocytes was similar to controls. The liver contains a low number of CD4 + and CD8 + cells in portal tracts and scattered through the parenchyma [28] but chronic liver injury is usually associated with inflammatory infiltrates [27,29]. The predominance of CD8 + infiltrating cells herein described and the increased expression of IFN-γ strongly suggest the presence of a local cytotoxic response in the liver of pediatric patients with NASH.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Through the same functional study based on ROS generation, oxygen metabolism of circulating monocytes was similar to controls. The liver contains a low number of CD4 + and CD8 + cells in portal tracts and scattered through the parenchyma [28] but chronic liver injury is usually associated with inflammatory infiltrates [27,29]. The predominance of CD8 + infiltrating cells herein described and the increased expression of IFN-γ strongly suggest the presence of a local cytotoxic response in the liver of pediatric patients with NASH.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously described the distribution of MN cell subpopulations in portal tracts and periportal and lobular areas of the liver [27]. Herein, the immunophenotype of MN cells infiltrating the portal tracts was characterized by immunohistochemistry and quantified in liver biopsies from ten patients with NASH.…”
Section: Analysis Of Liver Biopsiesmentioning
confidence: 99%
“…The repertoire of triggering antigens that can stimulate T and B cell activity in autoimmune hepatitis is small,37 but other defects in the immune regulatory network can amplify or perpetuate the cytotoxicity of sensitized immunocytes 34–36. The apoptotic pathway responsible for immunocyte depletion may be impaired, and the survival of autoreactive cells may be prolonged 38.…”
mentioning
confidence: 99%
“…Others have failed to obtain evidence in support of a significant role for apoptosis in the pathogenesis of AIH. An immunohistochemical study by De Biasio et al [23], for example, has reported that Fas-L and Bak apoptotic markers are uniformly distributed through the portal and periportal areas in liver biopsy specimens from patients with AIH-1 and chronic hepatitis C virus infected patients.…”
Section: Pathogenesis Of Autoimmune Hepatitismentioning
confidence: 99%